Healthy eating and lifestyle in pregnancy (HELP): a cluster randomised trial to evaluate the effectiveness of a weight management intervention for pregnant women with obesity on weight at 12 months postpartum - Robles, Jose Antonio; Simpson, Sharon A.; Coulman, Elinor; Gallagher, Dunla; Jewell, Karen; Cohen, David; Newcombe, Robert G.; Huang, Chao; Robles-Zurita, José Antonio; Busse, Monica; Owen-Jones, Eleri; Duncan, Donna; et al. (International journal of obesity, 2021)
Objective: To assess whether a weight management intervention for pregnant women with obesity was effective in reducing body mass index (BMI) 12 months after giving birth. Methods: Pragmatic, cluster randomised controlled trial (RCT) with embedded cost-effectiveness analysis. 598 women with a BMI of ≥30 kg/m2 (between 12 and 20 weeks gestation) were recruited from 20 secondary care maternity units in England and Wales. BMI at 12 months postpartum was the primary outcome. A range of clinical and behavioural secondary outcomes were examined. Interventions: Women attending maternity units randomised to intervention were invited to a weekly weight management group, which combined expertise from a commercial weight loss programme with clinical advice from midwives. Both intervention and control participants received usual care and leaflets on diet and physical activity in pregnancy. Results: Mean (SD) BMI at 12 months postpartum was 36.0 kg/m2 (5.2) in the control group, and 37.5 kg/m2 (6.7) in the intervention group. After adjustment for baseline BMI, the intervention effect was −0.02 (95% CI −0.04 to 0.01). The intervention group had an improved healthy eating score (3.08, 95% CI 0.16 to 6.00, p < 0.04), improved fibre score (3.22, 1.07 to 5.37, p < 0.01) and lower levels of risky drinking at 12 months postpartum compared to the control group (OR 0.45, 0.27 to 0.74, p < 0.002). The net incremental monetary benefit was not statistically significantly different between arms, although the probability of the intervention being cost-effective was above 60%, at policy-relevant thresholds. Conclusions: There was no significant difference between groups on the primary outcome of BMI at 12 months. Analyses of secondary outcomes indicated improved healthy eating and lower levels of risky drinking. Trial registration: Current Controlled Trials ISRCTN25260464.
Keywords: Lifestyle modification; Weight management